ETHICS AND ACCOUNTABILITY IN GOVERNANCE: PANACEA FOR EFFECTIVE AND EFFICIENT PUBLIC SERVICE DELIVERY IN NIGERIA: Array - Egugbo, Cletus (Acta Universitatis Danubius. Administratio, 2022)
Government all over the world exists to provide essential services to the citizens because that is the only way the citizens can feel the positive impact of governance. This paper examined the effects of ethics and accountability in governance on effective and efficient public service delivery. There cannot be effective and efficient public service delivery if there is the absence of ethics and accountability in governance in the public sector. Those who carry out the task of governance are given the power by the citizens and as such expected to ensure that the power given is used to deliver efficient and effective public services. This paper is qualitative in nature because data for the paper were gathered through secondary means and analyzed through the historical and descriptive methods. The paper adopted the social contract theory as theoretical framework. The paper found out that the low level of public service delivery in Nigeria which has manifested in high level of unemployment, poverty and insecurity is as a result of lack of strict adherence to ethics and accountability by those saddled with the responsibility of delivering public services in Nigeria. The paper recommended amongst other things that the citizens must be alive to their responsibility of ensuring they hold government and its officials to account for their actions and inactions and be ready to throw away inefficient government through elections and other legitimate means.